2015
DOI: 10.1016/j.jse.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of radiographic viewing perspective and demographics on the critical shoulder angle

Abstract: Background Accurate assessment of the critical shoulder angle (CSA) is important in clinical evaluation of degenerative rotator cuff tears. This study analyzed the influence of radiographic viewing perspective on the CSA, developed a classification system to identify malpositioned radiographs, and assessed the relationship between the CSA and demographic factors. Methods Glenoid height, width and retroversion were measured on 3D CT reconstructions of 68 cadaver scapulae. A digitally reconstructed radiograph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 43 publications
6
133
1
5
Order By: Relevance
“…Due to improvements in the resolution, a b c e d radiation exposure and length of examination of CT scans as well as the availability of 3D reconstruction software, preoperative planning for surgical procedures involving the reconstruction of glenohumeral osseous structures has been significantly facilitated [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Due to improvements in the resolution, a b c e d radiation exposure and length of examination of CT scans as well as the availability of 3D reconstruction software, preoperative planning for surgical procedures involving the reconstruction of glenohumeral osseous structures has been significantly facilitated [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the original study first introducing the concept of the CSA, authors reported variability of ≤2° in measuring the CSA with malrotations of the scapula of up to 20° of internal rotation or extension and 20° of external rotation or flexion 8. However, in a biomechanical study of 68 non-pathological cadaver shoulders, the authors found that the radiographic alignment of the scapula in anteversion and retroversion can yield highly inaccurate measurements of the CSA 39. More specifically, a 5°–8° change in viewing perspective can result in a 2° change in CSA 39.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a biomechanical study of 68 non-pathological cadaver shoulders, the authors found that the radiographic alignment of the scapula in anteversion and retroversion can yield highly inaccurate measurements of the CSA 39. More specifically, a 5°–8° change in viewing perspective can result in a 2° change in CSA 39. Henceforth, given the small range of non-pathological CSA values (30°–35°),8 clinicians must be careful to have appropriate shoulder/scapula positioning in order to avoid significant miscalculations of the CSA.…”
Section: Discussionmentioning
confidence: 99%
“…A second group of 119 patients diagnosed with adhesive capsulitis and normal radiographs served as controls. Only 326 (21%) of 1552 radiographs were of sufficient quality to measure the CSA due to the influence of scapular position on boney landmarks as defined by Suter et al [10]. Patients with cuff tears had a slightly higher (mean of 2°) CSA, but the CSA was not different between enlarging and stable tears, it did not change over time, and it did not correlate with baseline tear length.…”
Section: Radiographic Studiesmentioning
confidence: 99%